PENGARUH WORK-LIFE BALANCE TERHADAP WORK ENGAGEMENT MELALUI KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA KARYAWAN BPJS KETENAGAKERJAAN KANTOR CABANG MOJOKERTO - Winda Mahira; Khoirur Rozaq (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to examine the effect of work-life balance on work engagement with job satisfaction as a mediating variable among employees at the BPJS Ketenagakerjaan Mojokerto Branch Office. A quantitative approach was used with a census method involving 40 respondents. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.2.9. The results show that work-life balance does not directly affect work engagement but has a significant positive effect on job satisfaction. Furthermore, job satisfaction has a significant positive effect on work engagement and successfully mediates the relationship between work-life balance and work engagement. These findings highlight the critical role of job satisfaction in enhancing employee engagement through improved work-life balance.